2014
DOI: 10.3109/02699052.2014.919528
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation therapy after acquired brain injury in Argentina: Psychosocial outcomes in connection with the time elapsed before treatment initiation

Abstract: Overall, results suggest that CRT is associated with positive results in different areas of the psychosocial domain and that post-injury time can mediate this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The results strengthen earlier findings concerning the importance of cognitive rehabilitation within the first year after ABI for functional outcome (27,28,32), psychological well-being (30), and vocational functioning (29,65). Our data strongly support cognitive rehabilitation within the first 3-4 months after ABI for patients with attention impairment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results strengthen earlier findings concerning the importance of cognitive rehabilitation within the first year after ABI for functional outcome (27,28,32), psychological well-being (30), and vocational functioning (29,65). Our data strongly support cognitive rehabilitation within the first 3-4 months after ABI for patients with attention impairment.…”
Section: Discussionsupporting
confidence: 89%
“…However, the path of spontaneous recovery of cognitive functions after ABI is described as non-linear during that timeframe, with different physiological mechanisms and a steeper curve during the first 3-4 months (24). Consequently, data were collected from 2 cohorts (18) since, during the past decade, several studies have reported positive effects of subacute cognitive rehabilitation (< 3 months) after ABI (25)(26)(27)(28)(29)(30)(31)(32). These studies reported substantial changes during inpatient rehabilitation.…”
Section: Lay Abstractmentioning
confidence: 99%
“…injury is associated with greater improvements in mood, cognitive functioning, quality of life 138,142 and better functional outcomes 140, than treatment that begins late post-injury.…”
Section: Accepted Manuscriptmentioning
confidence: 99%